Helminth communities and host-parasite relationships in argentine brown rat (Rattus norvegicus) - Gomez Villafañe, Isabel Elisa (2008)
The aims of this research were: 1) to determine the helminth parasite fauna of seventy two Rattus norvegicus (Berkenhout, 1769) individuals inhabiting poultry farms in the Pampean region of Argentina; 2) to examine the relationship between parasitism and individual characteristics of the hosts, and 3) to analyze the associations among helminths. The study was carried out in twenty-four poultry farms from autumn 2000 to winter 2001. Nematodes were found in the intestine or caecum rectum of the 74 % of rats and cestodes were found along all the intestine of the 28 % of rats. Heterakis spumosa (Travassos 1914) was a central species, whereas Syphacia muris, Yamaguti 1941, Nippostrongylus brasiliensis (Travassos 1914) and Hymenolepis diminuta (Rudolphi 1819) were satellite species. Helminths do not affect rat survival and growth of rats. Rats parasitized with H. spumosa and H. diminuta were larger and older than non-parasitized rats. The intensity of infection with H. spumosa significantly increased with rat age. Rats parasitized with Nippostrongylus brasiliensis and Syphacia muris did not differ in size and age with respect to non-parasitized ones. The mean intensity of infections per host was 33.74, 74.28, higher than 200, and 3.10 for H. spumosa, S. muris, N. brasiliensis and H. diminuta, respectively. The mean intensity of infection with H. spumosa was higher in summer than in the other seasons, while the higher mean intensity of infection with N. brasiliensis and S. muris occurred in autumn. Infections with Heterakis spumosa and Syphacia muris, and with Syphacia muris and Nippostrongylus brasiliensis were independent; while Heterakis spumosa and Nippostrongylus brasiliensis were negatively associated.